Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2x+2 + 2x = 40
2x . 22 + 2x = 40
2x . 4 + 2x . 1 = 40
2x . ( 4 + 1 ) = 40
2x . 5 = 40
2x = 40 : 5
2x = 8
2x = 23
=> x = 3
a)(4-x)2+15=40
(4-x)2=40-15
(4-x)2=25
(4-x)2=52
=>4-x=5
x=5-4
x=1
a) ( 4 - x )2 + 15 = 40
( 4 - x )2 = 40 - 15
( 4 - x )2 = 25
( 4 - x )2 = 52
4 - x = 5
x = 4 - 5
x = ( - 1 )
b, ( 3x - 2 )10 = ( 3x - 2 )4
=> x \(\in\left\{0;1\right\}\)
c, X = 1 + 4 + 42 + ......... + 42017
4X = 4 + 41 + ......... + 42018
4X - X = ( 4 + 41 + ........ + 42018 ) - ( 1 + 4 + 42 + ......... + 42017 )
4X - X = 4 + 41 + ......... + 42018 - 1 - 4 - 42 - ......... - 42017
=> 3X = 42018 - 1
=> X = \(\frac{4^{2018}-1}{3}\)
a. 5(x+35)=515
=> x+35=515:5
=> x+35=103
=> x = 103-35
=> x = 68
b. (x+40).15=75.12
=>(x+40).15=900
=>x+40=900:15
=>x+40=60
=>x=60-40
=>x=20
c.460+85.4=(x+200):4
=>460+340=(x+200):4
=>800=(x+200):4
=>800.4=x+200
=>3200=x+200
=>x=3200-200
=>x=3000
b) (x + 15) - 51 = 72.24-1
(x + 15) - 51 = 49.16-1
(x + 15) - 51 = 784 - 1
(x + 15) - 51 = 783
(x + 15) = 783 + 51
x + 15 = 834
x = 834 - 15
x = 819
Vậy x = 819
c) 3125 - 25.(x + 40) = 1717
3125 - 32.(x + 40) = 1717
- 32.(x + 40) = 1717 - 3125
- 32.(x + 40) = -1408
x + 40 = -1408 : (-32)
x + 40 = 44
x = 44 - 40
x = 4
Vậy x = 4
d) 16 - x : 4 = 14
- x : 4 = 14 - 16
- x : 4 = -2
- x = -2.4
- x = -8
x = 8
Vậy x = 8
a) 72 - 23 . x = 0
\(\Rightarrow2^3.x=72\)
\(\Rightarrow8.x=72\)
\(\Rightarrow x=72:8=9\)
1) x - 36 + 12 = - x+ 10
=> x + x = 10 + 24
=> 2x = 34
=> x = 34/2 = 17
2) (x + 15) - (11 - x) = (-2)2
=> x + 15 - 11 + x = 4
=> 2x = 4 - 4
=> 2x = 0
=> x = 0
3) 40 - 4x2 = (-6)2
=> 40 - 4x2 = 36
=> 4x2 = 40 - 36
=> 4x2 = 4
=> x2 = 1
=> x = \(\pm\)1
4) (-50) + 10x2 = (-25) x |-2|
=> -50 + 10x2 = -50
=> 10x2 = -50 + 50
=> 10x2 = 0
=> x2 = 0
=> x = 0
5) |x + 1| = 2020
=> \(\orbr{\begin{cases}x+1=2020\\x+1=-2020\end{cases}}\)
=> \(\orbr{\begin{cases}x=2019\\x=-2021\end{cases}}\)
6) (x + 1)5 + 8 = 0 (xem lại đề)
7) (-20) + x3 : 16 = -24
=> x3 : 16 = -24 + 20
=> x3 : 16 = -4
=> x3 = -4 . 16
=> x3 = -64 = (-4)3
=> x = -4
9) x14 = x17
=> x14 - x17 = 0
=> x14(1 - x3) = 0
=> \(\orbr{\begin{cases}x^{14}=0\\1-x^3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
10) (-36) + (1 - x)2 = 0
=> (1 - x)2 = 36
=> (1 - x)2 = 62
=> \(\orbr{\begin{cases}1-x=6\\1-x=-6\end{cases}}\)
=> \(\orbr{\begin{cases}x=-5\\x=7\end{cases}}\)
\(\left(5^2+3^2\right).x+\left(5^2-3^2\right).x-40.x=10^2\)
\(\Rightarrow\left(25+9\right)x+\left(25-9\right)x-40x=100\)
\(\Rightarrow34x+16x-40x=100\Rightarrow\left(34+16-40\right)x=100\)
\(\Rightarrow10x=100\Rightarrow x=100\div10=10\)
Vậy \(x=10\)
=> 2^x-1 . ( 1 + 2^2 ) = 40
=> 2^x-1 . 5 = 40
=> 2^x-1 = 40 : 5 = 8
=> 2^x-1 = 2^3
=> x-1 = 3
=> x = 3+1 = 4
Vậy x = 4
Tk mk nha
`#3107.101107`
$2^{x + 2} + 2^x = 40$
$\Rightarrow 2^x . 2^2 + 2^x = 40$
$\Rightarrow 2^x . (2^2 + 1) = 40$
$\Rightarrow 2^x . 5 = 40$
$\Rightarrow 2^x = 40 \div 5$
$\Rightarrow 2^x = 8$
$\Rightarrow 2^x = 2^3$
$\Rightarrow x = 3$
Vậy, $x = 3.$
2x+2 + 2x = 40
2x+2= 2x . 22
2x . 22 + 2x = 40
2x(22+1) = 40
2x(4+1) = 40
2x . 5 = 40
2x = 40 : 5
2x = 8
2x = 23
=> x = 3
Vậy x=3